Review of three little-known monotypic empidoid genera (Diptera: Empidoidea: Brachystomatidae), assigned to Trichopezinae - Sinclair, Bradley J. (Zootaxa, 2008)
The monotypic genera Boreodromia Coquillett, Ceratempis Melander and Sematopoda Collin are reviewed with redescriptions of their respective type species and distributions outlined. The male and female terminalia of B. bicolor (Loew) and C. longicornis Melander are here described and illustrated for the first time. The male terminalia of S. elata Collin are illustrated in detail for the first time. The assignment of these genera to the Trichopezinae is discussed.